Spinal paraganglioma at the conus medullaris mimicking schwannoma: A case report. (October 2022) - Al-Salihi, Mohammed Maan; Hussein, Muath; Al-Jebur, Maryam Sabah; Rahman, Sabrina; Ayyad, Ali; Rahman, Md Moshiur
Abstract: Background: Paragangliomas of the spine are extremely rare, and they should be considered in the differential diagnosis of spinal tumors due to its overlapping clinical and radiological features with many spinal tumors. Case report: In this article, we present a 30-year-old lady who presented with low back pain and radicular neuropathic pain at L1 dermatome which was intractable to medical surgery. Her magnetic resonance imaging (MRI) of the lumbosacral spine revealed a T1 isointense, T2 heterogeneously hyperintense intradural extramedullary lesion at the conus medullaris with strong homogenous enhancement on contrast administration. The lesion was surgically excised completely with L1 laminectomy, and the histopathological picture was suggestive of paraganglioma. The patient's complaints resolved fully postoperatively, and there was no evidence of recurrence on long-term follow-up. Conclusion: Due to the absence of pathognomonic clinical or radiological features of paragangliomas, they should be taken into consideration in the differential diagnosis of spinal tumors. They share similar clinical and radiological features of schwannomas, ependymomas, and hemangioblastomas. The diagnosis is usually made postoperatively based on histopathological examination. Highlights: Paragangliomas overlap the clinical and radiological features with other tumors. Diagnosis is made postoperatively based on histopathological examination. It should be considered in the differential diagnosis of spinal tumors.